High responsivity n-ZnO nanorods/p-GaN heterojunction-based UV-A photodetectors. (1st January 2023) - Francis, Bellarmine; Sebastian, Reethu; Dixit, Tejendra; Ganapathi, K Lakshmi; Rao, M S Ramachandra
Abstract: Here, we report the fabrication of ZnO/p-GaN based high responsivity ultraviolet (UV) photodetector. Hydrothermal technique has been followed to grow ZnO nanorods; where two different types of precursors (nitrate and chloride) were used for the growth of nanorods. Interestingly, it was found that the ZnO nanorods grown using nitrate precursor are less prone to defect emission in comparison to the ZnO nanorods prepared using chloride-based precursor which resulted in low dark current levels. The photo-responsivity and photo-detectivity values of the as-fabricated device were calculated to be 350 mA W −1 and 3.5 × 10 11 Jones, respectively at 360 nm excitation wavelength and ∼1.79 µ W cm −2 excitation intensity. The demonstration of high responsivity UV detectors (at low excitation intensity values) using ZnO nanorods/GaN can pave the way toward the development of high-performance next generation UV photodetectors.